2016
DOI: 10.1109/tthz.2016.2557724
|View full text |Cite
|
Sign up to set email alerts
|

Integrated On-Chip THz Sensors for Fluidic Systems Fabricated Using Flexible Polyimide Films

Abstract: AbstractÑWe investigate the use of an on-chip terahertz (THz) frequency sensor formed on a flexible, thin-film polyimide substrate to measure the properties of liquids encapsulated in a glass-walled capillary. We observe changes in the attenuation and velocity of the time-domain THz signal, which allows extraction of the broadband THz refractive index and relative attenuation coefficients of the liquid. The technique is used for sensing members of a homologous series of primary alcohols, and the results compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In order to obtain the transmission spectra (S 21 ) of the waveguide with five integrated SRRs, two-port S-parameter simulations were performed. The THz signals were generated from wave-ports directly coupled to the PGL, as previously demonstrated in experiments [ 9 , 25 ]. We note that, using this method, the PGL mode is formed without a coplanar waveguide to PGL transition [ 26 ].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…In order to obtain the transmission spectra (S 21 ) of the waveguide with five integrated SRRs, two-port S-parameter simulations were performed. The THz signals were generated from wave-ports directly coupled to the PGL, as previously demonstrated in experiments [ 9 , 25 ]. We note that, using this method, the PGL mode is formed without a coplanar waveguide to PGL transition [ 26 ].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…108 With respect to compactness, the integrated method is more applicable to excite THz SPWs on PGLs. 54,100,109 Based on the above-mentioned waveguide method for PGLs, Dazhang et al 100 integrated a photoconductive antenna in the region of parallel CPWs, on top of which a small patch of low-temperature GaAs was deposited, as shown in Fig. 2(f).…”
Section: Direct Excitationmentioning
confidence: 99%
“…The same group also demonstrated that THz SPWs on a PGL could be excited by removing the ground planes at the two sides of the central structure connected to the PGL, which could help increase the frequency resolution. 54,109…”
Section: Direct Excitationmentioning
confidence: 99%
See 2 more Smart Citations